Study of Uniform and Localized Corrosion Behaviour of Aluminum Alloy 1050 as Al/AgO Battery Anode in Aerated NaCl in the Presence of an Organosulfur Inhibitor. Issue 14 (5th November 2020) - Peirow Asfia, Mohammad; Pourfarzad, Hamed; Kashani, Hamideh; Olia, Mohammad Hamed; Badrnezhad, Ramin
Abstract : The corrosion behavior and the battery performance of the Aluminum alloy 1050 as an anode in Al/AgO battery in aerated 3.5% NaCl solution, are evaluated in the presence of thiourea as an organic inhibitor, using different approaches, such as potentiodynamic polarization, electrochemical impedance spectroscopy, electrochemical noise analysis, field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and galvanostatic discharge. The results indicate that by the addition of inhibitor, the corrosion rate of the aluminum reduces at the initial stages, and by formation of a protective layer on the surface, pits initiation and propagation are controlled. With increasing the immersion time, inhibitor on the surface is provided a situation which aluminum as a battery anode can corrode uniformly and provides needed electron and capacity for battery with a better performance. According to shotnoise and stochastic theory, the probability of formation of pits with a radius of more than 20 μ is reduced significantly in the presence of inhibitor. Also, as it can be seen in the SEM results, aluminum tends to be corroded more uniform, which resulted in an anode efficiency of 91 percent in the galvanostatic discharge test.